Investigating the Impact of Strategies Used in Contextualization and Structures Toward Teaching English Words for EFL University Students - Alhodairy, Yusuf (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of the study was to find out the impact of strategies used in contextualization and structures toward teaching English words for Libyan EFL university students. The used a pretest and a posttest. The participants in this study were 65 students from a university in Sebha learning English as a foreign language (EFL) with their 2 English language teachers. The students were divided into two groups. The result showed that contextualization was effective for high performers (HPs) regarding contextual speaking and writing. Strategies used in structures effective for average performers (APs) and low performers (LPs). The average performers (APs) and low performers (LPs) taught by the structural strategies had better performance due to analyzing words morphologically, and the students’ participation and collaboration with each other.